The Effect of Social Media Advertising on Purchase Intention (Study on Students of SD/MI equivalent in the City of Bandung/Cimahi) - Abin Muhamad Farhan; Agus Rahayu; Puspo Dewi (Dinasti Publisher, 2023)
Education is very important in acquiring knowledge. In Indonesia, private schools need to be more creative in order to continue to grow, demonstrate competitive advantage and pay attention to core competencies. If the school services it produces are good, then trust will increase and make Purchase Intention very significant. The purpose of this research is to identify how Social Media Advertising influences Purchase Intention of SMP Daarut Tauhiid Boarding School. From the hypothesis test shows that there is a positive relationship from Social Media Advertising to Purchase Intention. The data analysis used is simple linear regression. The random sampling technique was used in conjunction with the directional sampling technique. Currently, the sample size is 103 people who live in the city of Cimahi and have never sent their children to Daarut Tauhiid Boarding School Middle School. The results of this study indicate that Social Media Advertising partially or simultaneously has a positive and significant effect on consumer purchase intentions for SMP Daarut Tauhiid Boarding School services.